Novel molecular changes induced by Nrg1 hypomorphism and Nrg1-cannabinoid interaction in adolescence: a hippocampal proteomic study in mice - Spencer, Jarrah R.; Darbyshire, Keturah M.; Boucher, Aurelie A.; Kashem, Mohammed A.; Long, Leonora E.; McGregor, Iain S.; Karl, Tim; Arnold, Jonathon C. (Frontiers in Cellular Neuroscience, 2013)
Neuregulin 1 (NRG1) is linked to an increased risk of developing schizophrenia and cannabis dependence. Mice that are hypomorphic for Nrg1 (Nrg1 HET mice) display schizophrenia-relevant behavioural phenotypes and aberrant expression of serotonin and glutamate receptors. Nrg1 HET mice also display idiosyncratic responses to the main psychoactive constituent of cannabis, Δ9-tetrahydrocannabinol (THC). To gain traction on the molecular pathways disrupted by Nrg1 hypomorphism and Nrg1-cannabinoid interactions we conducted a proteomic study. Adolescent wildtype (WT) and Nrg1 HET mice were exposed to repeated injections of vehicle or THC and their hippocampi were submitted to 2D gel proteomics. Comparison of WT and Nrg1 HET mice identified proteins linked to molecular changes in schizophrenia that have not been previously associated with Nrg1. These proteins are involved in vesicular release of neurotransmitters such as SNARE proteins; enzymes impacting serotonergic neurotransmission, and; proteins affecting growth factor expression. Nrg1 HET mice treated with THC expressed a distinct protein expression signature compared to WT mice. Replicating prior findings, THC caused proteomic changes in WT mice suggestive of greater oxidative stress and neurodegeneration. We have previously observed that THC selectively increased hippocampal NMDA receptor binding of adolescent Nrg1 HET mice. Here we observed outcomes consistent with heightened NMDA-mediated glutamatergic neurotransmission. This included differential expression of proteins involved in NMDA receptor trafficking to the synaptic membrane; lipid raft stabilization of synaptic NMDA receptors; and homeostatic responses to dampen excitotoxicity. These findings uncover for the first time novel proteins altered in response to Nrg1 hypomorphism and Nrg1-cannabinoid interactions that improves our molecular understanding of Nrg1 signaling and Nrg1-mediated genetic vulnerability to the neurobehavioural effects of cannabinoids.